2019
DOI: 10.1111/bcpt.13212
|View full text |Cite
|
Sign up to set email alerts
|

The impact of human CES1 genetic variation on enzyme activity assessed by ritalinic acid/methylphenidate ratios

Abstract: The present clinical trial investigated the impact of selected SNPs in CES1 on the metabolic activity of the enzyme. For this purpose, we used methylphenidate (MPH) as a pharmacological probe and the d‐RA/d‐MPH (metabolite/parent drug) ratios as a measure of enzymatic activity. This metabolic ratio (MR) was validated against the AUC ratios (AUCd‐RA/AUCd‐MPH). CES1 SNPs from 120 volunteers were identified, and 12 SNPs fulfilling predefined inclusion criteria were analysed separately, comparing the effect of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 24 publications
0
21
2
Order By: Relevance
“…For TDM of methylphenidate, sampling of plasma at 1-2 h after immediate release or between 5 and 8 h for extended-release formulations are recommended [19]. Stage et al [30] suggested the ritalinic acid/methylphenidate metabolic ratio based on a singlepoint measurement, 3 h after dose (10 mg, Ritalin®) as a marker of CES1 activity. The time point was chosen because of a high correlation with the corresponding AUC ratios (r ≥ 0.90) from 3 h and onwards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For TDM of methylphenidate, sampling of plasma at 1-2 h after immediate release or between 5 and 8 h for extended-release formulations are recommended [19]. Stage et al [30] suggested the ritalinic acid/methylphenidate metabolic ratio based on a singlepoint measurement, 3 h after dose (10 mg, Ritalin®) as a marker of CES1 activity. The time point was chosen because of a high correlation with the corresponding AUC ratios (r ≥ 0.90) from 3 h and onwards.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling closer to dosing may also be more convenient for the patients. The agreement between the two methods (AUC ratios and single-point measurements of metabolite/parent drug) needs to be further studied to assess which ratios and what timepoints would be most relevant for prediction of CES1 activity [30].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, PMs are more likely to experience improvement in ADHD symptoms, but due to their absence of CYP2D6 metabolic activity, they are at also at increased risk of having side effects from atomoxetine and may therefore require lower doses. From a pharmacodynamic perspective, there are a number of interesting findings warranting further investigation related to dopamine and norepinephrine disposition in the brain (e. g., COMT), as well as the contribution of genetic variability in CES1 (carboxylesterase 1) to methylphenidate metabolism [55]. However, the clinical efficacy and utility of testing for these genes remains unknown.…”
Section: Adhd Medicationsmentioning
confidence: 99%
“…Genetic variations in CES1, the gene encoding for the CES1 enzyme in the liver, have been shown to impact the enzyme activity towards different substrates in vitro [ 9 ], which could account for differences in MPH hydrolysis among patients. Nevertheless, very little is known about the stability of the drug and whether this could contribute to its low bioavailability in the gut [ 10 , 11 ]. Only recently, the absorption of MPH was modelled based on physicochemical properties of the drug, formulation-related information, and differences in gut physiology along the gastrointestinal tract [ 12 ].…”
Section: Introductionmentioning
confidence: 99%